Investigação experimental dos efeitos da vibração mecânica na técnica biospeckle laser para aplicação em equipamentos portáteis - Castro, Daniel Bernardes de (2020)
The dynamic laser speckle (DLS) and biospeckle laser (BSL) are techniques developed based on the processing of optical interference patterns formed when a laser light strikes a dynamic surface, such as a paint drying, or biological, like seeds, leaves or fruits. These non-destructive and non-invasive image processing techniques are used to quantify the activity level of biological or non-biological samples. Several studies were already developed in different areas, from Agriculture to Medicine. It has been observed in recent years an increase in the number of applications and publications about the use of the technique. Despite the expressive results, such studies, in general, are developed in a laboratory environment. The on-site application is necessary for the advancement of the technique in the commercial scope, since it is not always feasible to move biological samples to a laboratory to be analyzed. However, there are limitations in the use of the technique in the field. Obtaining an integrated and compact experimental configuration, a laser and power supply stability, and also prevents external noise interference, such as luminosity and vibration mainly, are challenges that the technique needs to face regarding the portability. Few studies have been carried out in this sense. Studies show that the BSL technique is sensitive to external vibrations, and aiming to understand the level of these interferences as well as to propose ways to mitigate them, in this work it was developed a portable prototype for SLD analysis. This equipment was subjected to various vibration tests, such as experimental modal analysis and transmissibility. SLD tests were performed in parallel. The prototype’s natural frequencies were obtained. It was evaluated how the optical technique behaves when excited at these and other frequencies, in a range from 0 to 1000 Hz. It was discovered that BSL is more sensitive to low frequencies, close to 5 Hz. In the transmissibility tests, where the vibration transmissibility of 11 vibration isolators was analyzed, it was found that the isolator with the lower stiffness presented the best characteristics of vibration isolation for the proposed purposes, making possible the portability of the prototype from the isolation of ordinary external mechanical vibrations.